Australia's first national exhibition of art, film & video Melbourne, 18 - 27 Nov. 1988 Experimenta - Hogan, Terence ([Australia] : Experimenta, 1988)
Features a black and white photograph of a woman taken from behind as she leans back in a chair while holding a cigarette to her lips.
Catalogue record generated as part of a batch load.
Also available online
Keywords: Motion pictures -- Australia -- Exhibitions -- Posters; Multimedia (Art) -- Australia -- Posters